ANALISIS KETERAMPILAN PROSES SAINS MENGGUNAKAN PEER ASSESSMENT PADA PEMBELAJARAN INKUIRI TERBIMBING DAN DIRECT INSTRUCTION - Fera Mulyasari; Nengah Maharta; Undang Rosidin (Jurnal Pembelajaran Fisika, 2013)
This study aims to know: (1) difference KPS assessed by student through peer assessment and teacher on guided inquiry learning; (2) difference KPS assessed by student through peer assessment and teacher on direct instruction; (3) interaction between assessor of KPS with learning model. Based on the study, data gathered in KPS assessed by student of peer assessment and teacher. The analysis results showed that the data distributed normally and homogeneously. The results of the study showed that: (1) there was difference KPS assessed by student through peer assessment and teacher on guided inquiry learning; (2) there was difference KPS assessed by student through peer assessment and teacher on direct instruction; (3) there was no interaction between assessor of KPS with learning model.Kata kunci: KPS, pembelajaran langsung, penilaian sejawat